Variable number of tandem repeat polymorphisms of the interleukin-1 receptor antagonist gene IL-1RN: a novel association with the athlete status - Ryckman Kelli K; Di Santolo Manuela; Cauci Sabina; Williams Scott M; Banfi Giuseppe (BMC, 2010)
Abstract Background The interleukin-1 (IL-1) family of cytokines is involved in the inflammatory and repair reactions of skeletal muscle during and after exercise. Specifically, plasma levels of the IL-1 receptor antagonist (IL-1ra) increase dramatically after intense exercise, and accumulating evidence points to an effect of genetic polymorphisms on athletic phenotypes. Therefore, the IL-1 family cytokine genes are plausible candidate genes for athleticism. We explored whether IL-1 polymorphisms are associated with athlete status in European subjects. Methods Genomic DNA was obtained from 205 (53 professional and 152 competitive non-professional) Italian athletes and 458 non-athlete controls. Two diallelic polymorphisms in the IL-1β gene (IL-1B) at -511 and +3954 positions, and a variable number tandem repeats (VNTR) in intron 2 of the IL-1ra gene (IL-1RN) were assessed. Results We found a 2-fold higher frequency of the IL-1RN 1/2 genotype in athletes compared to non-athlete controls (OR = 1.93, 95% CI = 1.37-2.74, 41.0% vs. 26.4%), and a lower frequency of the 1/1 genotype (OR = 0.55, 95% CI = 0.40-0.77, 43.9% vs. 58.5%). Frequency of the IL-1RN 2/2 genotype did not differ between groups. No significant differences between athletes and controls were found for either -511 or +3954 IL-1B polymorphisms. However, the haplotype (-511)C-(+3954)T-(VNTR)2 was 3-fold more frequent in athletes than in non-athletes (OR = 3.02, 95% CI = 1.16-7.87). Interestingly, the IL-1RN 1/2 genotype was more frequent in professional than in non-professional athletes (OR = 1.92, 95% CI = 1.02-3.61, 52.8% vs. 36.8%). Conclusions Our study found that variants at the IL-1ra gene associate with athletic status. This confirms the crucial role that cytokine IL-1ra plays in human physical exercise. The VNTR IL-1RN polymorphism may have implications for muscle health, performance, and/or recovery capacities. Further studies are needed to assess these specific issues. As VNTR IL-1RN polymorphism is implicated in several disease conditions, athlete status may constitute a confounding variable that will need to be accounted for when examining associations of this polymorphism with disease risk.